THE RELATION OF PRICE AND RED CHILI PRODUCTION IN BATURAJA OGAN KOMERING ULU REGENCY - Asidawati, Asidawati; Yetty Oktarina; Fifian, Fifian Permata Sari (International Journal of Social Science, 2022)
The purpose of this study was to analyze the existence and level of market integration of red chili and the relationship between prices and red chili production in Ogan Komering Ulu (OKU) Regency. This research was conducted in East Baturaja District, OKU Regency. This study uses monthly Times Series data for 5 years from 2017-2021. The research method used was library research method and the analytical tool used in this research is a VAR model approach to prove the existence of red chili market integration in the Ogan Komering Ulu Regency, East Baturaja District. Data processing is carried out with the Eviews program.6. The variables in this study were measured using the data stationarity test, determining the optimal lag level, cointegration analysis, impulse response analysis and variance decomposition. The results showed that all research variables, namely the price and production of chili in each short-term period, tend to adjust to each other to achieve long-term equilibrium. The results of the VECM analysis show that there is a short-term and long-term relationship between research variables.